2014
DOI: 10.7314/apjcp.2014.15.5.1913
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Intervention Program on Knowledge of Oral Cancer among the Youth of Jazan, Saudi Arabia

Abstract: Background: The study is the first of its kind to be conducted in Saudi Arabia (KSA), aiming to analyze the effectiveness of an intervention program in improving the knowledge of oral cancer among the youth. Materials and Methods: A total of 1,051 young Saudis (57% males and 43% females with a mean age of 20.4±1.98) were selected using multi-stage cluster sampling. Knowledge assessment was accomplished using a closed-ended questionnaire which was subjected to reliability tests. Prevalence of risk factors in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…This finding is also in consistent with several earlier reports citing buccal mucosa as the frequent site for oral cancer in shammah users 1. The prevalence of oral cancer remained constant and high over the study period due to the lack of public awareness,31 relevant health services and preventive actions. The relatively small number of benign neoplastic cases in relation to malignant neoplasms (1:4.5) in our series could be as these cases are not often referred or biopsied.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is also in consistent with several earlier reports citing buccal mucosa as the frequent site for oral cancer in shammah users 1. The prevalence of oral cancer remained constant and high over the study period due to the lack of public awareness,31 relevant health services and preventive actions. The relatively small number of benign neoplastic cases in relation to malignant neoplasms (1:4.5) in our series could be as these cases are not often referred or biopsied.…”
Section: Discussionsupporting
confidence: 92%
“…Only less than quarter of the participants knew that presence of red and or white patches was early signs of oral cancer. These findings are consistent with most of the published studies that reported lack of public knowledge regarding early signs of oral cancer (Tomar et al, 2005;Devadiga and Prasad 2010;Pakfetrat et al, 2010;Park et al, 2011;Agrawal et al, 2012;Saleh et al, 2012;Tadbir et al, 2013;Quadri et al, 2014). Such findings indicate that there is not enough attempt on giving information about first signs of oral cancer, and that is why most of people have not enough information about that (Tadbir et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…This underscores the need for an extensive awareness campaigns on the issues related to oral cancer. It has been reported that public awareness of oral cancer is low (Park et al, 2011;Agrawal et al, 2012;Ghani et al, 2013;Tadbir et al, 2013;Quadri et al, 2014); and several studies have shown that oral cancer awareness is lesser when compared with other types of cancer (Pakfetrat et al, 2010;Park et al, 2011;Rogers et al, 2011). Moreover, it has been reported that the majority of certain populations failed to recognize the early signs and symptoms of oral cancer (Ghani et al, 2013;Tadbir et al, 2013;Quadri et al, 2014).…”
Section: Public Awareness and Knowledge Of Oral Cancer In Yemenmentioning
confidence: 99%
“…Jazan region is reported to have the highest number of oral cancer cases diagnosed each year in the Kingdom of Saudi Arabia (Quadri et al, 2014). A previous retrospective longitudinal study conducted from 1976 till 1995 using the data obtained at the King Faisal specialist hospital and research center in Riyadh revealed that 35.4% of all the oral cancer cases from the nation were just from one province namely, Jazan (Allard et al, 1999).…”
Section: Discussionmentioning
confidence: 99%